Hubungan Kepatuhan Terapi Antihiperglikemia Terhadap Terkontrolnya HbA1c pada Pasien Terdiagnosa Diabetes Melitus Tipe 2 di RSU Prima Medika, Denpasar - Ariyanti, Ni Kadek Nining; Virginia, Dita Maria; Hendra, Phebe (Jurnal Farmasi Udayana; Vol. 13, No. 1, Tahun 2024, 2024)
Diabetes mellitus is a disease caused by chronic metabolic disorders accompanied by increased blood glucose levels. Adherence to treatment is very important to achieve therapeutic success in type 2 diabetes mellitus (T2DM) patients and prevent complications. HbA1c value is one of the parameters used to see the success of T2DM therapy. This study was conducted to determine the relationship between compliance with antihyperglycemic therapy for T2DM patients and the patient's HbA1c value. This study used a cross-sectional research design and data collection was carried out by non-random sampling with purposive sampling technique. The research subjects were 100 T2DM patients at RSU Prima Medika Denpasar, Bali with the age of 40-70 years. The level of patient compliance in taking medication was measured by the Medication Possession Ratio (MPR) method based on patient treatment records. The results showed 78% aged 40-59 years, 53% female, 86% T2DM with comorbidities 62% received combination therapy, 87% were compliant with taking medication. There was no significant relationship between the characteristics of T2DM patients and compliance (p-value > 0.05). There was a significant association between medication adherence and controlled HbA1c values in patients with T2DM (p-value < 0.05; OR (95%CI) : 4,902 (1,026 - 23,430)).